CHALLENGES AND STRATEGIES IN THE IMPLEMENTATION OF ENGLISH SYLLABUS IN HIGHER EDUCATION - Normawati, Afi; Putra, Daffa Alamsyah; Manggolo, Noor Sahid Kusuma Hadi; Nugrahaeni, Dwitiya Ari (STKIP Persada Khatulistiwa Sintang, 2025)
The implementation of an English syllabus in higher education often reveals a gap between the planned curriculum and actual classroom practice. While this is a known issue, limited research has explored the specific challenges and strategies from the perspective of lecturers in the Indonesian university context. This study addresses this gap by investigating the difficulties lecturers face and the adaptive strategies they employ. This research utilised a qualitative descriptive method, gathering data through semi-structured interviews and classroom observations with English language lecturers from several Indonesian universities. The findings reveal that challenges in syllabus implementation are caused by both internal and external factors. The internal factor is the significant variation in students’ English proficiency level, which is often linked to students’ motivation gap and limited English language practice, leading to the needs for differentiated learning in the classroom. The external factor is the world rapid change, which requires teaching materials to remain relevant and updated. In addition, time constraints further complicate the implementation. To manage these, lecturers apply strategies such as differentiated teaching, strategic code-switching, material updates, and flexible time management. Importantly, lecturers perceive these adaptations not as a misalignment with the syllabus, but as a necessary and professional flexibility to meet students' needs. The study concludes that effective syllabus implementation is a dynamic process of adaptation rather than rigid adherence. A collaborative approach between syllabus designers and implementers, combined with continuous evaluation, is essential to ensure the syllabus remains a relevant and effective tool that can respond to diverse student needs.